2007
DOI: 10.1093/jac/dkm112
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR strategy for subtyping the staphylococcal cassette chromosome mec type IV in methicillin-resistant Staphylococcus aureus: ‘SCCmec IV multiplex’

Abstract: This new strategy, based on a single multiplex PCR reaction, is adequate for the rapid assignment of all major subtypes of SCCmec type IV described so far and also the new subtype IVh characteristic of EMRSA-15. This strategy complements well the previously described multiplex PCR assay for the rapid assignment of SCCmec types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(94 citation statements)
references
References 26 publications
2
90
0
2
Order By: Relevance
“…The structure of the staphylococcal cassette chromosome mec (SCCmec) was determined by multiplex PCR (20), and SCCmec type IV subtyping was done by multiplex PCR (21). Ambiguous results were further tested by amplification of the ccrB gene (22) and comparing the sequences obtained with the ccrB typing tool available at the Instituto de Tecnologia Quimica e Biologica (ITQB) in Portugal.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the staphylococcal cassette chromosome mec (SCCmec) was determined by multiplex PCR (20), and SCCmec type IV subtyping was done by multiplex PCR (21). Ambiguous results were further tested by amplification of the ccrB gene (22) and comparing the sequences obtained with the ccrB typing tool available at the Instituto de Tecnologia Quimica e Biologica (ITQB) in Portugal.…”
Section: Methodsmentioning
confidence: 99%
“…The genetic struc-ture of the staphylococcal cassette chromosome mec element (SCCmec) and the presence of Panton-Valentine leukocidin (PVL) virulence factor genes (lukS-PV and lukF-PV) were also determined (2,(12)(13)(14). MLST analysis revealed that the mecC-carrying isolate belongs to sequence type 130 (ST130) (CC130).…”
mentioning
confidence: 99%
“…Basically, the structures of SCCmec consist of a mec gene complex which houses the mecA gene and its regulatory elements, a cassette chromosome recombinases (ccr) complex, and the flanking direct repeat sequences that contain the integration site sequence for SCC. SCCmec is classified based on the combination of ccr gene complex and the class of the mec gene complex, whereas subtyping of SCCmec is performed on basis of the polymorphisms or variations in J re-gions (6)(7)(8)(9). At present, a total of 11 main types of SCCmec with sizes ranging from 20.9 kb to 66.9 kb have been defined by International Working Group on the Staphylococcal Cassette Chromosome Elements (IWG-SCC) based on their structural features (10).…”
Section: Introductionmentioning
confidence: 99%